2015
DOI: 10.1179/1467010015z.000000000276
|View full text |Cite
|
Sign up to set email alerts
|

Using singing to nurture children's hearing? A pilot study

Abstract: This article reports a pilot study of the potential benefits of a sustained programme of singing activities on the musical behaviours and hearing acuity of young children with hearing impairment (HI). Twenty-nine children (n=12 HI and n=17 NH) aged between 5 and 7 years from an inner-city primary school in London participated, following appropriate ethical approval. The predominantly classroom-based programme was designed by colleagues from the UCL Institute of Education and UCL Ear Institute in collaboration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 50 publications
0
21
0
1
Order By: Relevance
“…In addition, it has been reported that early music experiences can have a beneficial impact on a wide range of developmental features embracing cognitive, emotional, physical, and social domains. Example studies include those by Bengtsson et al (2005), Chen et al (2012), Creech et al (2016), Dingle et al (2012), Eerola and Eerola (2013), Forgeard et al (2008), Fujioka et al (2006), Gaser and Schlaug (2003), Gordon et al (2015), Habib et al (2016), Halwani et al (2011), Hetland (2000), Ho et al (2003), Hyde et al (2009), Knight et al (2016), Masataka and Perlovsky (2012), Moreno and Besson (2006), Moreno et al (2009), Nutley et al (2014), Osborne et al (2016), Pantev et al (2001), Paulson et al (2013), Rickard et al (2010), Roden et al (2012), Saunders et al (2014), Schlaug et al (2005), Seinfeld et al (2013), Tierney et al (2013), Trappe (2012), Welch et al (2014), Welch et al (2015), Wetter et al (2009), and Williams et al (2015). For overviews of such impacts, see Hallam (2015), Schlaug (2015), Silvia et al (2016) and—for a more discursive narrative—see Henriksson-Macauley (2014).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…In addition, it has been reported that early music experiences can have a beneficial impact on a wide range of developmental features embracing cognitive, emotional, physical, and social domains. Example studies include those by Bengtsson et al (2005), Chen et al (2012), Creech et al (2016), Dingle et al (2012), Eerola and Eerola (2013), Forgeard et al (2008), Fujioka et al (2006), Gaser and Schlaug (2003), Gordon et al (2015), Habib et al (2016), Halwani et al (2011), Hetland (2000), Ho et al (2003), Hyde et al (2009), Knight et al (2016), Masataka and Perlovsky (2012), Moreno and Besson (2006), Moreno et al (2009), Nutley et al (2014), Osborne et al (2016), Pantev et al (2001), Paulson et al (2013), Rickard et al (2010), Roden et al (2012), Saunders et al (2014), Schlaug et al (2005), Seinfeld et al (2013), Tierney et al (2013), Trappe (2012), Welch et al (2014), Welch et al (2015), Wetter et al (2009), and Williams et al (2015). For overviews of such impacts, see Hallam (2015), Schlaug (2015), Silvia et al (2016) and—for a more discursive narrative—see Henriksson-Macauley (2014).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Another study reported an enhancement of F0 discrimination following 2-36 months of musical schooling [61]. Finally, one valuable intervention study reported the same enhancement after two school terms of weekly musical training, although not related to speech-in-noise perception amelioration [45].…”
Section: Pitchmentioning
confidence: 93%
“…The use of technologyto provide visual feedback may be particularly successful with the DS group, in line with previous studies with TD populations. Specifically, visual feedback should be used to provide information to the performer about their performance, enabling 'knowledge of results' (Welch, 1998;Welch, Howard & Rush, 1989), especially in those with HI (Welch et al, 2015). Although the present study relied on gestural and simple visual forms of support and feedback, the availability and accessibility of mobile technology make this a useful tool for supporting accuracy in musical skills (e.g.…”
Section: Wider Implications and Recommendationsmentioning
confidence: 99%
“…Evidence from the bimanual drumming studies (Ringenbach et al, 2006;Chen et al, 2015) suggests benefits for visual modality over auditory-verbal modes for DS participants. In TD populations, visual teaching strategies have led to improvements in rhythmic skills (Sadakata, Hoppe, Brandmeyer, Timmers & Desain, 2008), violin pitchplaying skills (Wang, Wang, Chen, Chang, & Chen, 2012) and singing skills (Howard, Brereton, Welch, Himonides, DeCosta, Williams, & Howard, 2007;Wilson, Lee, Callaghan & Thorpe, 2008), including children with HI (Welch, Saunders, Edwards, Palmer, Himonides, Knight et al, 2015). Such research with people with DS is limited, but visuo-spatial instruction has successfully improved piano skills in individuals with DS (Velasquez, 1991, cited in Peters, 2000.…”
mentioning
confidence: 99%